2021
DOI: 10.1111/cns.13765
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin ameliorates cognitive impairment by activating mitophagy and suppressing neuroinflammation in rats with sepsis‐associated encephalopathy

Abstract: Background Fisetin, the effective ingredient of the traditional Chinese medicine named Cotinus coggygria, is recommended to be active therapeutic in many disorders. However, its role in sepsis‐associated encephalopathy (SAE) remains unclarified. Methods Cecal ligation and puncture (CLP) operation was performed to establish a rat model of SAE. Rats were grouped according to the surgery operation and fisetin administration. Cognitive impairment was assessed by Morris water maze test. Disruption of blood‐brain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Therefore, we investigated the ROS scavenging activity of fisetin and found that fisetin significantly repressed H 2 O 2 -induced ROS generation. This is in good agreement with the results of previous studies ( Zhao et al, 2019 ; Rodius et al, 2020 ; Molagoda et al, 2021 ; Ding et al, 2022 ) and suggests that fisetin may act as an oxidative stress blocker. Several previous studies have proven that oxidative stress-induced apoptosis by H 2 O 2 treatment in ARPE-19 cells is directly correlated with mitochondrial impairment ( Zhao et al, 2020 ; Hong et al, 2021b ; Kim et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, we investigated the ROS scavenging activity of fisetin and found that fisetin significantly repressed H 2 O 2 -induced ROS generation. This is in good agreement with the results of previous studies ( Zhao et al, 2019 ; Rodius et al, 2020 ; Molagoda et al, 2021 ; Ding et al, 2022 ) and suggests that fisetin may act as an oxidative stress blocker. Several previous studies have proven that oxidative stress-induced apoptosis by H 2 O 2 treatment in ARPE-19 cells is directly correlated with mitochondrial impairment ( Zhao et al, 2020 ; Hong et al, 2021b ; Kim et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have demonstrated that fisetin has multiple pharmacological activities such as neuroprotective, anti-inflammatory, chemopreventive, anti-angiogenic, anti-tumorigenic, anti-cancer activities without showing any appreciable toxicity ( Zhu et al, 2017 ; Mehta et al, 2018 ; Liang et al, 2020 ; Maher, 2021 ; Ravula et al, 2021 ). More interestingly, although excessive accumulation of ROS may be a major factor in fisetin-induced apoptosis of cancer cells ( Su et al, 2017 ; Tsai et al, 2019 ; Imran et al, 2021 ), the protective effects of fisetin against cell damage to various stimuli are associated with potent antioxidant activity by acting as a potent ROS scavenger ( Zhao et al, 2019 ; Rodius et al, 2020 ; Molagoda et al, 2021 ; Ding et al, 2022 ). Moreover, several previous studies have demonstrated that this compound can modulate the Nrf2/antioxidant response elements (AREs) pathway to exert antioxidant activity ( Sim et al, 2020 ; Jiang et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous drugs or chemical components have been used to ameliorate sepsis‐induced cognitive dysfunction and neuroinflammation in mice. These include traditional Chinese medicine, 26 acetylcholinesterase inhibitors, 27 angiotensin‐converting enzyme (ACE) inhibitors, 28 the benzodiazepine agonist MRK‐016, 29 the NMDA antagonist MK‐801, 30 ketamine, 31 morphine, 32 morin, 33 and others. Among these strategies, SAE prevention and treatment is achieved mainly via anti‐inflammatory and antioxidative interventions which indicates the importance of inflammatory pathways and oxidative stress in SAE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was well known that the antioxidant effects of fisetin could be attributable to the activation of Nrf2/HO-1 [ 22 ]. However, Fisetin also blocked NLRP3 inflammasome activation and inhibited the release of IL-1β into the CNS in rats with encephalopathy [ 23 ]. Therefore, this study was planned to explore the protective effect of fisetin on VaD, pointing to the contribution of NF-κB/NLRP3 inflammasome and NRF2/HO-1 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%